Consolidação processual e substancial na recuperação judicial - Fernandes, Melina Martins Merlo (2022)
The purpose of this work is to analyze the judicial reorganization of a group of companies with a focus on substantial and procedural consolidation. Although the institute is not new, its discussion in Brazilian Courts is current and is related to the consequences of the political-economic crisis that the country is going through. For the development of this study, research was also carried out on the subject at the Court of Justice of the State of São Paulo, in order to verify the use of procedural and substantial consolidation in Brazilian law. The analysis of the case law before and after the reform of the Bankruptcy and Judicial Reorganization Law made it possible to identify the grounds invoked in the decisions for the application of procedural and substantial consolidation and controversial issues, such as the form of presentation of the list of creditors and the recovery plan court, the form and quorum of voting and the consequences of approving or rejecting the consolidation. In the end, some criticisms were made in relation to the legal amendment instituted by Law n. 14.112/2020, which inserted Section IV-B into Law n. 11.101/2005 and began to expressly discipline the procedural and substantial consolidation in articles 69-G to 69-L